2021
DOI: 10.1089/nat.2020.0860
|View full text |Cite
|
Sign up to set email alerts
|

Mesyl Phosphoramidate Oligonucleotides as Potential Splice-Switching Agents: Impact of Backbone Structure on Activity and Intracellular Localization

Abstract: A series of 2'-deoxy and novel 2'-O-methyl and 2'-O-(2-methoxyethyl) (2'-MOE) oligonucleotides with internucleotide methanesulfonyl (mesyl, μ) or 1butanesulfonyl (busyl, β) phosphoramidate groups have been synthesized for evaluation as potential splice-switching oligonucleotides. Evaluation of their spliceswitching activity in spinal muscular atrophy (SMA) patient derived fibroblasts revealed no significant difference in splice-switching efficacy between 2'-MOE mesyl oligonucleotide and the corresponding phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…This reaction between the esters of 3′,5′-dinucleoside phosphites and organic azides has been used previously to introduce N -sulfonylphosphoramide groups and N -alkylphosphoramide groups , into the oligonucleotide. The phosphoryl guanidine and mesyl phosphoramidate oligonucleotides are particularly important as potential splice-switching agents …”
Section: Introductionmentioning
confidence: 99%
“…This reaction between the esters of 3′,5′-dinucleoside phosphites and organic azides has been used previously to introduce N -sulfonylphosphoramide groups and N -alkylphosphoramide groups , into the oligonucleotide. The phosphoryl guanidine and mesyl phosphoramidate oligonucleotides are particularly important as potential splice-switching agents …”
Section: Introductionmentioning
confidence: 99%
“…In summary, the present work and recently published article 48 show that various sulfonyl phosphoramidate oligonucleotides can be used in combination with other modifications to provide altered sugar-phosphate backbone and modulate the activity of oligonucleotides which can be applied for splice modulation.…”
Section: Discussionmentioning
confidence: 58%
“…It was also noted that the use of a different pentose sugar (2′-deoxy vs. 2′-OMe ribose vs. 2′-MOE-ribose) in combination with a different phosphate modification (PS vs. Ms- vs. Bs-) alters the level of endosomal release and cellular localisation, which is pivotal for exon-skipping processes occurring in the nucleus of the cell. 48 It was argued that lower activity of Ms- and Bs- 2′-OMe or 2′-MOE AOs in vivo could be explained by compromised endosomal release and/or nuclear uptake of these AOs in comparison with their PS-analogues. One should note that a combination of PS and phosphoramidate modifications in one AO was not evaluated in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To inhibit miRNA activity, we applied recently developed chemically modified antisense oligonucleotides, containing mesyl phosphoramidate (µ) modification of internucleotidic phosphates. These antisense µ-ONs were proven to exhibit high therapeutic potential in a number of studies [ 24 , 25 , 26 , 27 ]. Notably, our recent research showed the outstanding stability, superior RNase H-activating ability, long-lasting and specific downregulation of miRNA targets, and high biological performance of µ-oligonucleotides in tumor cells.…”
Section: Introductionmentioning
confidence: 99%